The influence of the Jarimatika-assisted CLIS model on motivation and mathematics learning outcomes - Nurhayati Selvi; Ulfiani Rahman; Wahyullah Alannasir; Juan Astuti (Journal Focus Action of Research Mathematic (Factor M), 2026)
Mathematics learning at SDN Inpres Wadu Wani, which remains teacher-centered, has resulted in low student motivation, conceptual understanding, and classroom activity. Without more innovative and student-centered approaches, this condition may hinder the development of mathematical thinking skills and the achievement of optimal learning outcomes. This study aimed to analyze the improvement of students’ motivation and mathematics learning outcomes after implementing the CLIS model assisted by Jarimatika. The study employed a quantitative approach with a one-group pretest–posttest experimental design. The sample consisted of 18 third-grade students in the even semester of the 2024–2025 academic year selected through saturated sampling. Data were collected using validated and reliable motivation questionnaires and learning outcome tests. Data analysis included normality testing, t-test, Wilcoxon test, N-Gain analysis, and effect size calculation to determine the significance and magnitude of improvement after treatment. The findings showed that the average motivation score increased from 35.78 (SD = 8.71) to 43.06 (SD = 5.51), with significant differences (t = -8.438; p < 0.001), an N-Gain of 0.512, and an effect size of 1.99. Learning outcomes also improved from 60.00 (SD = 21.42) to 78.33 (SD = 17.24), with significant differences (Z = -3.796; p < 0.001), an N-Gain of 0.458, and an effect size of 0.895. These results indicate that integrating Jarimatika-based calculation techniques supports students' active participation and conceptual understanding. This study contributes to the development of innovative elementary mathematics learning strategies by implementing the Jarimatika-assisted CLIS model to enhance students’ motivation and learning outcomes.